High prevalence of fluoroquinolone‐resistant UTI among US emergency department patients diagnosed with urinary tract infection, 2018–2020. (5th August 2022) - Faine, Brett A.; Rech, Megan A.; Vakkalanka, Priyanka; Gross, Alan; Brown, Caitlin; Harding, Stephanie J.; Slocum, Giles; Zimmerman, David; Zepeski, Anne; Rewitzer, Stacey; Howington, Gavin T.; Campbell, Matt; et al.
Abstract: Background: Uropathogen resistance, fluoroquinolone‐resistance (FQR), and extended spectrum beta‐lactamase (ESBL), has been observed to be emerging worldwide with prevalences above recommended thresholds for routine empirical treatment. The primary aim of our study was to determine the prevalence of FQR from a geographically diverse sample of United States emergency departments (EDs). Methods: We conducted a multi‐center, observational cohort study using a network of 15 geographically diverse US EDs. All patients ≥18 years of age with the primary or secondary diagnosis of urinary tract infection (UTI) in the ED identified using International Classification of Diseases (ICD‐10) diagnosis code of cystitis, pyelonephritis, or UTI from 2018 to 2020 were included. We calculated descriptive statistics for uropathogens and susceptibilities. Logistic regression analysis was used to identify antimicrobial resistance risk factors associated with FQR Escherichia coli . Results: Among 3779 patients who met inclusion criteria, median age was 62.9 years (interquartile range [IQR]: 41–77.6) and 76.3% were female. The most common diagnoses were complicated (41.2%) and uncomplicated cystitis (40.3%). E. coli was the most common pathogen (63.2%), followed by Klebsiella pneumoniae (13.2%) and Enterococcus species (5.8%). Across all sites, overall E. coli FQ‐resistance prevalence was 22.1%, ranging from 10.5 to 29.7% by site. The prevalence of ESBL‐producing uropathogen was 7.4%, ranging from 3.6% to 11.6% by site. Previous IV or oral antimicrobial use in the past 90‐days and history of a multi‐drug resistant pathogen were associated with FQ‐resistant E. coli (odds ratio [OR] 2.68, 95% confidence interval [CI]: 2.04–3.51, and OR 6.93, 95% CI: 4.95–9.70, respectively). Of the patients who had FQ‐resistant E. coli or an ESBL‐producing uropathogen isolated, 116 (37.1%) and 61 (36.7%) did not have any documented risk factors for resistance. Conclusion: FQ‐resistant E. coli is widely prevalent across US sites highlighting the need for ongoing monitoring of antimicrobial resistance and, at some locations, modification of empirical treatments.